Analisis Distribusi Tegangan, Regangan, dan Perpindahan Prostesis Diskus Intervertebralis pada Posisi Fleksi - Zainal Abidin; Muhammad Fadly Ramadhan (Jurnal Rekayasa Mesin, 2022)
Total intervertebral disc replacement using prosthesis is one of treatments for degenerative intervertebral disc. This prosthesis must accommodate loads from the lumbar spine. This research performed an analysis of stress, strain, and displacement distribution of a ProDisc-L® prosthesis developed by Centinel Spine® installed on an L4-L5 segment of lumbar spine model of a 21 years old man. The simulation performed with two positions; standing upright and flexion, with loads applied are 750 N and 7,5 Nm respectively. Maximum Von Mises stress resulted from the standing upright and flexion simulations are 187,971 MPa and 555,113 MPa respectively. The stress on standing upright position can be considered safe as it is still below the yield stress of the endplate material (σy = 527 MPa), meanwhile the stress on flexion position can be considered unsafe as it is over the yield stress of the endplate material (σy = 527 MPa). Maximum strain resulted from the standing upright and flexion simulations are 3,9% and 1,7% respectively. Maximum displacement resulted from the standing upright and flexion simulations are 0,30 mm and 0,36 mm respectively, which can be concluded that the displacement was still under the maximum displacement allowed (1 mm).